(untitled) (Journal of actual problems of jurisprudence, 2019)
The question of becoming and developing of bii’s judge in Kazakh land is considered in this article. From the conclusion concerns that Kazakhs had their own original legislation, that the order of lan activity was effective and progressive. That is why we may exactly say that Kazakh had developed and effective system of law activity. It may be a good making law reforms as wellas the achievement of developed countries is necessary to analize and use its own historical experience.